Peningkatan Literasi Digital Guru SMA Dharma Amiluhur Melalui Pelatihan Video Animasi Plotagon - N, Nuryadi; Marhaeni, Nafida Hetty; Khuzaini, Nanang (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
For teachers, digital literacy is an important ability and skill to master. One form of digital literacy that is increasingly relevant is the ability to make animated videos. However, many teachers may not yet have the skills in using Plotagon or making animated videos in general. Therefore, special training is needed to improve the digital literacy of teachers at Dharma Amiruhur High School, especially in terms of making Plotagon-assisted animation videos. This service was carried out by a team of service from Universitas Mercu Buana Yogyakarta. Meanwhile, the service partner is SMA Dharma Amiluhur with participants being teachers at SMA Dharma Amiluhur totaling 12 people. The approach used is an active participation, activity orientation, program, and independence approach. The results of the service show that the implementation also shows that the success of the implementation of the service. The success can also be seen from the average results obtained showing that ?80% of participants have knowledge and understanding related to Plotagon animation videos. This service made the teachers of SMA Dharma Amiluhur as participants helped in the implementation of learning.